The experiences of social workers regarding occupational stress: a study in the department of social development, Capricorn District, Limpopo Province - Sekgobela, Mmakopa Annah (My University, 2021)
The social work profession experiences significant occupational stress caused by the changing working environment. Research has indicated that social workers are faced with various stressors in the work environment, such as unsatisfactory working conditions, role conflict, inadequate salaries and high caseloads. Even though there has been studies looking at stress in the workplace there seem to be a gap on studies looking at stress among social workers thus this study has endeavoured to explore the experiences of social workers employed by the Department of Social Development in Capricorn District, Limpopo regarding occupational stress. The study employed the interactive model of stress and the job demand-control model as a theoretical framework. The study used a qualitative approach and employed a case study research design. Purposive sampling was used to select 10 participants from social workers employed by Department of Social Development, Capricorn District, Limpopo. Data was collected using interviews, and one on one semi-structured interview method was used guided by interview guide. The study employed thematic analysis and the most important findings that emerged included poor infrastructure; lack of resources such as shortage of transport, telephones, printers and computers. Among other findings were lack of organisational support, relatively low compensation, and work overload, lack of control and autonomy, and cases related to children found to be stressful due to lack of support, planning and implementation form the department. The main conclusion drawn from the study was that social workers experience high levels of occupational stress due to various factors. This affected the social worker’s quality of work life and their interpersonal relationships as there is no adequate support provided by the department although there is Employee Assistance Programme (EAP) practitioner who does not afford services to all employees. Drawing from the participants’ experience of occupational stress, the study has also revealed various strategies used by social workers to cope with stress. Social workers continue to view their profession as valuable to the lives of communities despite the challenges they face daily. Various suggestions have been conceived to curb occupational stress
A report on a research study presented to the Department of Social Work, School of Human and Community Development, Faculty of Humanities, University of Witwatersrand, in partial fulfilment of the requirements for the degree Master of Arts in Social Work, 2021